SUPPLY CHAIN RESILIENCE AND SUSTAINABILITY OF CULINARY MSEs IN PADANG CITY DURING THE COVID-19 PANDEMIC (JURNAL ECONOMICA : Research of Economic And Economic Education, 2022)
This study aims to examine the effect of supply chain resilience on the sustainability opportunities of Culinary MSEs in Padang City during the Covid-19 Pandemic. This research used  primary data with survey method. The analytical technique used was the probit regression method with response variable is categorical, namely continuous business and discontinued business/bankrupt. The results showed that supply chain resilience consisted of 3 variables, namely the proactive capability and reactive capability are proven to have a significant effect on increasing the probability of the sustainability of culinary MSEs, while the supply chain design quality variable does not show a significant effect on the probability of the sustainability of   culinary MSEs. In addition, control variables such as the experience of MSEs, the age of the business owner, education, gender, and the number of workers did not have a significant effect on the probability of the sustainability of Culinary MSEs. It is recommended to existing Culinary MSEs to further improve the resilience of their supply chain especially at proactive capability and reactive capability as well as to the Government to be more active in distributing MSEs assistance, integration in the supply chain and training, especially the digitalization of MSEs to encourage the sustainability of Culinary MSEs in Padang City in facing crisis situations such as the Covid-19 Pandemic.